2018
DOI: 10.1111/bjh.15519
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the MCL35 gene expression proliferation assay in randomized trials of the European Mantle Cell Lymphoma Network

Abstract: Mantle cell lymphoma (MCL) is still considered incurable and the course of the disease is highly variable. Established risk factors include the Mantle Cell Lymphoma International Prognostic Index (MIPI) and the quantification of the proliferation rate of the tumour cells, e.g. by Ki-67 immunohistochemistry. In this study, we aimed to validate the prognostic value of the gene expression-based MCL35 proliferation assay in patient cohorts from randomized trials of the European Mantle Cell Lymphoma Network. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Additionally, mutations in the SWI/SNF (SWItch/Sucrose Non‐Fermentable) chromatic remodeling complex (including SMARCA4 mutations) have been recently identified and predict poor response to treatment with ibrutinib‐venetoclax in MCL. Recently, a NanoString RNA‐ expression‐based molecular assay (MCL35) with a 17‐gene proliferation signature was validated to predict prognosis in MCL patients treated with R‐CHOP or treated with intensive first line chemoimmunotherapy. In another study, a six‐gene signature ( AKT3 , BCL2 , BTK , CD79B , PIK3CD , and SYK) was predictive of poor outcome but higher sensitivity to ibrutinib .…”
Section: Advances In MCL Prognosticationmentioning
confidence: 99%
“…Additionally, mutations in the SWI/SNF (SWItch/Sucrose Non‐Fermentable) chromatic remodeling complex (including SMARCA4 mutations) have been recently identified and predict poor response to treatment with ibrutinib‐venetoclax in MCL. Recently, a NanoString RNA‐ expression‐based molecular assay (MCL35) with a 17‐gene proliferation signature was validated to predict prognosis in MCL patients treated with R‐CHOP or treated with intensive first line chemoimmunotherapy. In another study, a six‐gene signature ( AKT3 , BCL2 , BTK , CD79B , PIK3CD , and SYK) was predictive of poor outcome but higher sensitivity to ibrutinib .…”
Section: Advances In MCL Prognosticationmentioning
confidence: 99%
“…Clinical treatment information and patient outcome were not available on these retrospective cases to evaluate the prognostic power of the MCL35 in non-nodal samples. However, in a prior publication, the MCL35 risk assessment on 42 non-nodal samples (tonsils, gastrointestinal biopsies, soft tissue specimens, and other materials) was reported to correlate with overall survival [13].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we could not evaluate the prognostic power of the MCL35 in other types of non-nodal samples due to lack of clinical annotation. However, in a prior publication, the MCL35 risk assessment on 42 non-nodal samples was reported to correlate with overall survival [13].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, McCall et al presented a rare case of CD5-negative non-nodal MCL accompanied by TP53 mutation/17p deletion, but the patient still achieved long progression-free survival (PFS) [44]. Some studies have indicated that the higher the MCL risk group, the higher the percentage of patients with > 50% TP53 expression, and the expression of TP53 is related to the outcome of MCL independent of the MIPI and Ki-67 level [14,45]. However, some studies have suggested that stratifying patients by proliferation to separate them into low-, intermediate-and high-risk groups is more effective than stratifying them by any single driver mutation [45,46].…”
Section: Abnormal Expression Of Tp53mentioning
confidence: 99%
“…However, we found that the significance of IGHV mutations and the expression level of SOX11 in MCL are controversial [8]. In addition, there are many terms used to describe indolent MCL, such as leukemic non-nodal MCL, early-stage MCL, limited-stage MCL, low-risk MCL, and small-MCL [9][10][11][12][13][14][15]. After reviewing a large number of previous studies, we recommend that all indolent MCL presentations be unified under the title "smoldering mantle cell lymphoma (SMCL)".…”
Section: Introductionmentioning
confidence: 99%